2-pebbling property of butterfly-derived graphs. (15th December 2021) - Punitha, M. Joice; Suganya, A. Sagaya
For a graph G, f(G) is the least distribution of p pebbles on the vertices of G, so that we can move a pebble to any vertex by a sequence of moves and each move is taking two pebbles off one vertex and placing one pebble on an adjacent vertex. A graph G is said to satisfy 2-pebbling property, if it is possible to move two pebbles to any arbitrarily chosen vertex with a possible distribution of 2f(G) - q + 1 pebbles, where q is the number of vertices with at least one pebble. This paper determines the pebbling number and the 2-pebbling property of butterfly derived graphs.